Consistent Growth for Perpetual Sustenance: A Study of Select Banks - Kuchanur, Adinath Bhujaballi (Indian Journal of Finance, 2011)
The sustained growth and performance of a bank signify that it has a consistent growth in its sources and applications of funds over a period of time and also evidences the efficacy of its professional management. The funds grow up year after year as the growth and expansion are inevitable for a bank, and it perpetuates longer, provided that there is a consistent growth in its funds. A study on the growth, efficiency, performance, strength and soundness and profitability of banks, thus, assumes a great significance in the formulation of policies and setting the norms for the smooth and proper functioning. The present study analyzes the consistent growth in the sources and the applications of funds of four, each Public Sector Banks and Private Sector Banks and the data were collected for a period of ten years, i.e. from 2000 to 2009. This paper is an attempt to endorse that the consistent growth in both the funds is a strong indicator of perpetual sustenance in the life cycle of a bank. The main objective of the study is to assess the consistent growth in both the funds and to rank the banks. The hypotheses set for each variable were tested by t-Test value at 5% level of significance, and the fund wise and the sector wise ranks were assigned to each bank. The findings of the study reveal that Punjab National bank, ICICI bank and HDFC bank have a consistent growth, whereas, other banks have a less consistent growth in their funds during the study period. The study suggests that the depositors, the customers and the investors need to take into account the consistent growth in the funds of the bank while dealing with it from the safety point of view.